Serosurvey of viral pathogens in free-ranging dog populations in the high altitude Trans-Himalayan region - Home, Chandrima; Bijoor, Ajay; Bhatnagar, Yash Veer; Vanak, Abi Tamim (Journal of Threatened Taxa, 2022)
Dogs, as reservoir hosts, have been implicated in the decline of carnivore populations across the globe. We conducted a serosurvey of free-ranging dog populations to assess the population level exposure rates to three viral pathogens, canine parvovirus (CPV), canine distemper virus (CDV) and canine adenovirus (CAV) in a Trans-Himalayan landscape in India that is home to the endangered Snow Leopard. A total of 97 dogs were sampled across six villages as a part of a surgical sterilization campaign during the study period. Samples were tested for IgG antibodies using a table top ELISA kit. Exposure rates to the three viral pathogens in the dog populations was high; 100% for CPV, 54% for CDV and 66% for CAV, with high positive immunoglobulin titer values for CAV and CPV, and low to moderate values for CDV. Overall conservation efforts for native carnivores need to address the role of free-ranging domestic dogs in disease transmission.